Computation of the Nucleolus for a Class of Disjunctive Games with a Permission Structure - René van den Brink; Ilya Katsev; Gerard van der Laan (Tinbergen Institute, 2008)
A situation in which a finite set of players can obtain certain payoffs by cooperation can be described by a cooperative game with transferable utility, or simply a TU-game. A (single-valued) solution for TU-games assigns a payoff distribution to every TU-game. A well-known solution is the nucleolus. A cooperative game with a permission structure describes a situation in which players in a cooperative TU-game are hierarchically ordered in the sense that there are players that need permission from other players before they are allowed to cooperate. The corresponding restricted game takes account of the limited cooperation possibilities by assigning to every coalition the worth of its largest feasible subset. In this paper we provide a polynomial time algorithm for computing the nucleolus of the restricted games corresponding to a class of games with permission structure.
Keywords: C71; 330; TU-game; nucleolus; game with permission structure; peer group game; information market game; algorithm; complexity; Transferable Utility Games; Core; Kooperatives Spiel; Informationsmarkt; Soziale Beziehungen; Theorie